Theoretical-experimental behavior of steel fibers as a partial replacement for shear reinforcement in reinforced concrete beams - Juárez Alvarado, César Antonio; Mendoza Rangel, José Manuel; Terán Torres, Bernardo Tadeo; Valdez Tamez, Pedro Leobardo; Castruita Velázquez, Gregorio (Revista ALCONPAT, 2021)
It is proposed to partially replace the stirrups with steel fibers and thus improve the shear strength concrete beams. The following variables were studied: water/cement ratios (w/c) = 0.55 and 0.35 and fiber volume (Vf) = 0, 0.3, 0.5, 0.7% and 0, 0.2, 0.4, 0.6% respectively, as well as the separation of the stirrups. The experimental results showed that the shear strength of the fiber-reinforced and stirrups, was greater than the strength of the control beams with only stirrups at a separation of d/2. From the comparison between the experimental data and the mathematical models, it was found that both models adequately predict the effect of the w/c ratio, Vf, the contribution of longitudinal steel and the presence of stirrups in the ultimate strength to shear. The proposed models predicted in most cases conservative values with respect to the ultimate shear strength.